The limit-experience: following blanchot towards the other in speech and in Literature - Kutelas, Vanina Berin. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2008., 2008)
This thesis examines Maurice Blanchot's reflections on the human being's relation with the Other (Autrui) and/or Presence, notions that are impossible to experience and subsume under knowledge. Close readings of Blanchot's works "The Limit-Experience" and "Literature and the Right to Death" reveal human existence to be based on a duality of presencelabsence and investigate two modes of relation to Presence: speech and literature. Blanchot suggests that the human being's existence is based on exteriority while human life and human truth are oriented towards the reachievement of Unity- Identity. Thls need for Unity-Idenity causes the denial of the Other as such, manifested as the never-ending denial of Presence that is the basis for human action and knowledge. The limitexperience, Blanchot's interpretation of Bataille's "interior experience", signifies a moment of freedom from representation through which Presence offers itself As a way of reachmg the revelation of Presence, Blanchot proposes the game of "plural speech" wherein the space of attention generated between the interlocutors may allow for a glimpse of the "unlimited play of thought". Speech in general is postulated as a relation wherein the human being steps out of himself to receive the Other in the mutual space of attention, a space "in-between'' two human beings that allows for a glimpse of Presence. Literature, on the other hand, aiming to recreate the Presence of beings that is annihilated in language from notlung, serves to disclose the presence of language that is based on the absence of beings, mirroring the duality of presencelabsence at the heart of human existence.